2018
DOI: 10.3390/molecules23092385
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive In Silico Method to Study the QSTR of the Aconitine Alkaloids for Designing Novel Drugs

Abstract: A combined in silico method was developed to predict potential protein targets that are involved in cardiotoxicity induced by aconitine alkaloids and to study the quantitative structure–toxicity relationship (QSTR) of these compounds. For the prediction research, a Protein-Protein Interaction (PPI) network was built from the extraction of useful information about protein interactions connected with aconitine cardiotoxicity, based on nearly a decade of literature and the STRING database. The software Cytoscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 107 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…The presence of extracellular sodium, induced by AC, caused the reduced inactivation of the alpha subunits of the human heart (hH1) channels ( Wright, 2002 ). Wang et al reported that AC possessed binding stability for the receptor calcium-calmodulin–dependent protein kinase gamma (CAMK2G) ( Wang et al, 2018 ). Sun’s results indicated that AC significantly aggravated Ca 2+ overload and caused arrhythmia and finally promotes apoptotic development via phosphorylation of P38 mitogen-activated protein kinase ( Sun et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of extracellular sodium, induced by AC, caused the reduced inactivation of the alpha subunits of the human heart (hH1) channels ( Wright, 2002 ). Wang et al reported that AC possessed binding stability for the receptor calcium-calmodulin–dependent protein kinase gamma (CAMK2G) ( Wang et al, 2018 ). Sun’s results indicated that AC significantly aggravated Ca 2+ overload and caused arrhythmia and finally promotes apoptotic development via phosphorylation of P38 mitogen-activated protein kinase ( Sun et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our detection of ALDH2 is interesting as this gene is not only associated with alcohol dependence in humans, but is also an important regulator of dopaminergic and serotonergic systems implicated in protective effects against opioids addiction 48 and exhibits important interactions with the mescaline receptor 5-HT2A, responsible of the psychotropic effects and involved Reference populations: www.nature.com/scientificreports/ in several mental pathologies 49,50 . The expression of ATP2A1 has been related to the induced cardiotoxicity of alkaloids, suggesting an important role in maintaining calcium homeostasis during cardiac arrhythmia 51,52 , while CYP3A genes, members of the P-450 family gene, encode for one of the most important CYP isoforms (CYP3A4, CYP3A5, CYP3A7 and CYP3A43) responsible of alkaloids detoxification and clearance of psychotropic medication in humans 53,54 . These findings are in line with our detection of several psychotropic and toxic alkaloids in T. terscheckii.…”
Section: Discussionmentioning
confidence: 99%
“…aconitine ( Fig. 1a), also known as monkshood or devil's helmet, is a type of toxin produced by the aconitum plant that has been used as a traditional medicine in china due to its analgesic and anti-inflammatory effects (32). A previous study has indicated that aconitine can induce apoptosis in human pancreatic cancer cells via the nF-κB signaling pathway (33).…”
Section: Introductionmentioning
confidence: 99%